Guidance Strategy and Utilization of Artificial Intelligence (AI) in Writing Scientific Articles for Undergraduate Nursing Students - Moh. Zainudin; Eka Nurjanah (Universitas Pendidikan Ganesha, 2025)
Scientific article writing is a crucial competence for students in the AI-driven digital era. However, many students still struggle with idea organization, scientific reasoning, and academic language, highlighting the need for adaptive writing guidance. This study aims to analyze students’ perceptions and experiences of academic writing supervision and the use of AI in supporting the writing process. This study aims to analyze students’ perceptions and experiences of academic writing supervision and to explore the use of AI in supporting the scientific writing process. This study employed a descriptive qualitative approach involving undergraduate students who met the inclusion criteria, namely having experience in academic writing supervision and using AI tools in writing scientific articles. Data were collected through semi-structured interviews, observations, and document analysis, using interview guides, observation sheets, and relevant documents as research instruments. Data analysis was conducted through data reduction, data display, and conclusion drawing with verification. The findings indicate that structured and dialogic supervision enhances student engagement and understanding of scientific writing processes. AI use effectively supports idea development and language revision but requires ethical guidance. Integrating humanistic academic supervision with targeted AI use can sustainably improve scientific writing quality and strengthen curricula, lecturers’ competencies, and students’ digital literacy in higher education.